2004
DOI: 10.1128/jcm.42.8.3594-3599.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Distinguishes Mycobacterium africanum

Abstract: Mycobacterium africanum is thought to comprise a unique species within the Mycobacterium tuberculosis complex. M. africanum has traditionally been identified by phenotypic criteria, occupying an intermediate position between M. tuberculosis and M. bovis according to biochemical characteristics. Although M. africanum isolates present near-identical sequence homology to other species of the M. tuberculosis complex, several studies have uncovered large genomic regions variably deleted from certain M. africanum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 44 publications
2
89
2
1
Order By: Relevance
“…In various mycobacterial species, LSPs represent robust and accurate markers for mapping of chromosomal imbalances. In M. tuberculosis (15,32,58), Mycobacterium africanum (40), M. bovis (39), the vaccine strain M. bovis BCG (6,19), and in other mycobacteria (18,35,42,43,48), most known LSPs have been identified using microarray technologies. Previous identification of RDs in a collection of M. ulcerans patient isolates originating from different regions worldwide where BU is endemic suggested that a whole-genome microarray might lead to the identification of LSPs also at a regional level (47).…”
Section: Discussionmentioning
confidence: 99%
“…In various mycobacterial species, LSPs represent robust and accurate markers for mapping of chromosomal imbalances. In M. tuberculosis (15,32,58), Mycobacterium africanum (40), M. bovis (39), the vaccine strain M. bovis BCG (6,19), and in other mycobacteria (18,35,42,43,48), most known LSPs have been identified using microarray technologies. Previous identification of RDs in a collection of M. ulcerans patient isolates originating from different regions worldwide where BU is endemic suggested that a whole-genome microarray might lead to the identification of LSPs also at a regional level (47).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study the species were determined on the basis of a combination of biochemical testing and DNA typing (36). However, identification of mycobacterial strains has since improved by the use of chromosomal deletions (10,28,44,48), SNPs (28), and sequencing of the 16S rRNA gene DNA (8,33 (11,44,45). The latter designation was established after revision of the interpretative guidelines used for analysis of genetic data (44).…”
Section: Methodsmentioning
confidence: 99%
“…However, identification of mycobacterial strains has since improved by the use of chromosomal deletions (10,28,44,48), SNPs (28), and sequencing of the 16S rRNA gene DNA (8,33 (11,44,45). The latter designation was established after revision of the interpretative guidelines used for analysis of genetic data (44). The M. tuberculosis strains from this collection represent at least 17 genotype families or subfamilies, as determined by previous studies (35,36) and a large spoligotype database described by Filliol et al (17,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. africanum type II (lack of spacer 40) is isolated predominantly in Uganda (15), and although we obtained six spoligotypes lacking spacer 40, all of ours were aerophilic on Lebek media, which is not the case for M. africanum. Indeed, recent genomic analysis could not differentiate M. africanum subtype II from modern M. tuberculosis, casting doubt on whether subtype II should be considered separately from M. tuberculosis (14). In total, spoligotyping identified 13 strains with the Cameroon family spoligotype (lacking spacers 23 to 25).…”
mentioning
confidence: 99%